Anchovy (Stolephorus sp) Utilization at Coastal Waters of Tegal - Dian Sutono; Adi Susanto (JURNAL PERIKANAN DAN KELAUTAN, 2016)
Anchovy is one superior commodity from capture fishery sector in Tegal water with payang jabur fishing gear. Requesting for anchovy which keep on to increase that stimulate on business for payang jabur at Tegal water. However, increased to business for payang jabur not based for potensial of sustainable, so that threatening to sustainable in the habitat. The research is aimed to analyze in the level of utilization for anchovy resources with the CPUE analysis, the MSY analysis, the optimum effort analysis, and optimum for operation of payang jabur business. Data analyzed make to surplus production model (Schaefer model). It determined for fishing season used time series analyzed of CPUE with moving average. Anchovy production (1999 – 2011) in Tegal water increased average is 0,95% per year parallel with the addition for business unit is 30,62% per years and the addition for trip is 14.61% per years, while the CPUE decreased average 11.24% per years. The lowest of production on 2004 is 265.36% ton and highest of production on 2008 is 858.70 ton. The highest of effort on 2011 is 26,333 trip and the lowest of effort on 2003 is 6,308 trip. The highest of CPUE on 1999 is 105.67 kg/trip and the lowest of CPUE on 2011 is 15.70 kg/trip. The result of analysis showed the highest MSY is 665.65 ton/year with Fopt is 18,411 trip/year. The utilization of anchovy resources in Tegal water showed that over capacity on 2008 (112.91%); 2010 (129.13%); 2011 (143.03%) and over MSY on 1999 (126.46%) and 2008 (132.13%). Fishing season that accours throughout the years with IMP 77.75-123.32%.